Purchase intention towards family takaful products among lecturers in Universiti Teknologi MARA Kampus Bandaraya Melaka / Nur Syamimi Kamaruzuki and Zunnur Afiqah Ramlan - Kamaruzuki, Nur Syamimi; Ramlan, Zunnur Afiqah (Faculty of Business and Management, 2014)
This research is focused to conducting the study of purchase intention towards Family Takaful products among lecturers UiTM Kampus Bandaraya Melaka. Takaful is one the financial Islamic that provide by the Takaful Operator follow on Shariah Compliance. This research has four factors that influencing that purchase intention towards Family Takaful products among lecturers UiTM Kampus Bandaraya Melaka which are awareness, promotion, trust and religiosity. The objective of this study are (1) To analyse the elements that will attract lecturers to purchase Family Takaful (2) To invest whether product offerings plays an important role to enhance purchase of Family Takaful (3) To recommended in increasing purchasing Family Takaful products among lecturers in UiTM Kampus Bandaraya Melaka. The respondent are among lecturers in UiTM Kampus Bandaraya Melaka and 100 questionnaires has been distribute among them. The sampling technique that was researcher used is convenience technique. This researcher was done finding by using reliability test, descriptive statistic and correlation test. The result show that purchase intention towards Family Takaful products among lecturers UiTM Kampus Bandaraya Melaka is good but Takaful operator or organization still have to increase the awareness of people based on religiosity, make an improvement of promotion and increase the trust of customer toward Takaful to gain the profit on the organization.